Safety in the global south: Criminal victimization in Brazilian rural areas. (June 2015) - Scorzafave, Luiz Guilherme; Justus, Marcelo; Shikida, Pery Francisco Assis
Abstract: In this paper, we discuss our finding that crime was on the rise not only in Brazil's urban areas, but also in rural ones between 1988 and 2009. Its main objective is to investigating how different economic, demographic and other variables can help one understand criminal victimization in Brazilian rural areas. Data from a 2009 national survey were used to fit probit models for four types of crime: theft, robbery, attempted theft/robbery, and physical assault. Moreover, we estimated a model for a category that encompasses the three first crimes. We found that men, middle-age and single people in rural areas are at a higher risk of being victimized, as well as higher-income and more educated people living in those areas. Highlights: Crime raised in Brazilian rural areas between 1988 and 2009. Women and non-white people experienced higher victimization growth rates. Men are more victimized than women; larger families are less likely to be victimized. There is an inverted U relationship between age and victimization. There is a positive relationship between income and property crime victimization.